Effect of public health expenditure on health outcomes in Nigeria and Ghana - Ayomide Oluwaseyi Oladosu; Timothy Chanimbe; Uchechi Shirley Anaduaka (Elsevier, 2022)
Despite the prevailing literature examining the effect public health expenditure has on health outcomes in Africa, Malaria and HIV/AIDS mortality which are key indicators of the outcome variable were unconsidered when drawing inferences. In view of this oversight, we investigate the impact of public health expenditure on health outcomes in Nigeria and Ghana whilst reconceptualizing health outcome by capturing infant, maternal, Malaria and HIV/AIDS mortality. Using the health expenditure commitment at the 1999 United Nations General Assembly and the Abuja Declaration of 2000, we also assessed public policy's role in this relationship via linear regression analysis. With hindsight, our findings disclosed a low public health expenditure in both countries despite the Ghanaian case revealing a negative relationship, which was primarily insignificant whilst Nigeria indicated a positive one. These empirical evidences accentuate the need to augment public health expenditure in both countries to boost health outcomes whilst bringing to bear the significant influence of GDP, school enrolment and residing in urban areas on health outcomes.